Neck Shaft Angle of Non-articulated Femur Bones among Adults in Nepal - Shrestha, Anusuya; Ranjit, Nirju; Shrestha, Rajani (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The neck-shaft (collo-diaphysial) angle of the human femur bone is an important factor for the hip stability and normal walking. It has been described that neck shaft normally ranges from the angle of 115° to 140°. The main objective of the study is to evaluate the neck shaft angle of the non-articulated adult Nepalese femur bones. Methods: Altogether 100 non-articulated adult human femur bones with 50 right and 50 left were taken from a renowned anatomy laboratory. The femora were of unknown sex, age and race. Use of simple protector was used to measure the neck-shaft angle. Both the anterior and posterior views were observed and 200 measurements were recorded. Results:The mean value of neck shaft angle was 127.71°with standard deviation of 5.78°. The mean angle of 128.46° and 126.97° with the respective standard deviation of 5.83° and 5.66° were observed with respect to the right and left adult femur bones. Conclusion: The neck shaft angle of non-articulated adult femur bone of Nepalese people had no remarkable dissimilarity with the angles observed in the studies conducted in the neighboring countries. Neither was there any significant difference between the neck-shaft angle of right and left adult femur bones of the Nepalese.